Improved triethylamine sensing properties by designing an In2O3/ZnO heterojunction - Oliveira, Taís N.T. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Zito, Cecilia A. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2021)
Sensors of volatile organic compounds (VOCs) play a vital role in environmental monitoring. Although much progress has been made to develop new sensing materials, it remains challenging to detect a particular VOC selectively and without the interference of humidity. Herein, we report the effect of In2O3 nanoparticles on the VOC-sensing performance of ZnO twin-rods. The VOC-sensing tests were carried out in dry air and at a relative humidity (RH) of 26, 59, and 98%. The results indicated that the In2O3/ZnO heterostructure exhibited an improved sensing performance to triethylamine (TEA) compared to ZnO. In dry air, the responses to 100 ppm of TEA at 350 °C were 60.2 for the In2O3/ZnO heterostructure and 39.2 for pure ZnO. In2O3/ZnO even exhibited a high response of 6.2 to 1 ppm of TEA. Moreover, In2O3/ZnO exhibited a response to TEA up to 46.2 times higher than those of the other VOCs, indicating excellent selectivity. At 98% RH, the In2O3/ZnO heterostructure still had a high sensitivity to TEA, showing a response of 21.2 to 100 ppm of TEA with a response time of 1 s. The improved TEA-sensing performance of the In2O3/ZnO heterostructure can be attributed to the formation of the n-n heterojunction.
Keywords: Chemoresistive sensor; Microwave-assisted hydrothermal; N-n heterojunction; Ultrasonic spray nozzle; Volatile organic compounds